2015
DOI: 10.1515/chempap-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of non-standard reaction conditions for asymmetric 1,3-dipolar organocatalytic cycloaddition of nitrone with α,β-unsaturated aldehydes

Abstract: Non-standard experimental conditions can often enhance organocatalytic reactions considerably. The current study explores the effectiveness of a range of non-standard reaction conditions for the asymmetric organocatalytic 1,3-dipolar cycloaddition of a nitrone with α,β-unsaturated aldehydes. The influence of ionic liquids, high-pressure conditions, ultrasound, microwave irradiation and ballmilling was tested as well as the flow process. Because of the low reactivity of the nitrone and unsaturated aldehydes in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Asymmetric 1,3‐dipolar organocatalytic cycloaddition of nitrone 42 with α,β‐unsaturated aldehyde 43 proceeded under continuous‐flow conditions with high stereoselectivity. Isoxazoline 44 was obtained as only the endo diastereoisomer with 94 % ee (Scheme ) …”
Section: Organocatalysis In Flowmentioning
confidence: 99%
“…Asymmetric 1,3‐dipolar organocatalytic cycloaddition of nitrone 42 with α,β‐unsaturated aldehyde 43 proceeded under continuous‐flow conditions with high stereoselectivity. Isoxazoline 44 was obtained as only the endo diastereoisomer with 94 % ee (Scheme ) …”
Section: Organocatalysis In Flowmentioning
confidence: 99%
“…A mechanistic study of Diels-Alder reactions of selected anthracenes by Arrhenius kinetics was reported by Andersen and Mack [70]. The array of 1,3-dipolar cycloaddition reactions is recently extended with nitrones [71] and nitrile oxides [72].…”
Section: Synthesismentioning
confidence: 99%
“…In 2015, Šebesta and co-workers tested nine different organocatalysts and six ionic liquids ( Figure 3) in 1,3-dipolar cycloaddition of (Z)-N-benzylidene-1-phenylmethanamine oxide 66 with α,β-unsaturated aldehydes 67a-f (Scheme 12) [45].…”
Section: Synthesis Of Isoxazolines and Isoxazolidinesmentioning
confidence: 99%
“…In 2015, Šebesta and co-workers tested nine different organocatalysts and six ionic liquids ( Figure 3) in 1,3-dipolar cycloaddition of (Z)-N-benzylidene-1-phenylmethanamine oxide 66 with α,β-unsaturated aldehydes 67a-f (Scheme 12) [45]. Six ionic liquids (commercial or prepared according to the literature [45]) and two of nine organocatalysts tested in 1,3-dipolar cycloaddition of (Z)-N-benzylidene-1-phenylmethanamine oxide with α,β-unsaturated aldehydes [45]. Six ionic liquids (commercial or prepared according to the literature [45]) and two of nine organocatalysts tested in 1,3-dipolar cycloaddition of (Z)-N-benzylidene-1-phenylmethanamine oxide with α,β-unsaturated aldehydes [45].…”
Section: Synthesis Of Isoxazolines and Isoxazolidinesmentioning
confidence: 99%
See 1 more Smart Citation